Analytic hierarchy process (AHP) and the definition of attributes to support decision making: a bibliometric analysis - Gonçalves, Wellington; Rocha, Alessandro Roberto; Zatta, Fernando Nascimento; Santos, Diego Vieira dos (Brazilian Journal of Production Engineering, 2021)
Due to its high flexibility and wide applicability, different paths taken and points of view about the Analytic Hierarchy Process (AHP) have been extensively studied in the literature over the last 50 years. At the time this work was written, a bibliometric analysis on the state of the art of how criteria are being defined and measured in the use of AHP for managing activities and operations has not been identified. Thus, we performed a review in the Web of Science (WoS) database, using applied research articles, published between 1970 and 2020. Aspects such as citation and publication structure were used to organize the realization of the estimate of literary evolution through the software Zotero. We then employ VOSviewer software to map cocitation and co-occurrence. The results show a gradual increase in citation and publication structure, in addition to hybrid uses and applications, highlighting AHP as an important element for academia and also for the advancement of knowledge about aiding decision-making. This work contributes to science by identifying practices in the use of AHP, helping different people interested in the subject to understand the different paths and approaches given to the aspects of use.